Adhesiolysis and Decortication for Reccurent Hydropneumothorax Associated with Pleural Tuberculosis - Musthafa, Muhamad Yusuf; Sugiri, Yani Jane; Bayuadi, Imam Suseno (Universitaas Brawijaya, 2021)
Introduction: Pleural tuberculosis is a pleural infection of tuberculosis caused by Mycobacterium tuberculosis which commonly manifests as hydropneumothorax. Initial treatment with anti-tuberculosis drugs is aimed to prevent progression of the disease and relieve patient’s symptoms. Indication of adhesiolysis and decortication is to remove layer of fibrous tissue and allow the lung to reexpand.Case: A 60 year old woman with shortness of breath, cough, and right-sided chest pain. She had a history of treatment with first-line anti-tubercular drugs for a year stop in September 2016. She was identified with recurrent right-sided hydropneumothorax by chest imaging and thorax CT-scan. Adhesiolysis and decortication were performed on her. Two months later she was diagnosed again with recurrent right-sided hydropneumothorax. VATS (Video-Assisted Thoracoscopic Surgery) revealed fistula involving inferior lobe of the lung. Then, she was treated with second-line anti tuberculosis drugs. After four times reccurent hydropneumothorax, patient showed significant improvement in clinical condition, radiology finding, and lung function test after she finished the tuberculosis treatment.Discussion: Definitive diagnosis of pleural tuberculosis is by the finding of mycobacterium tuberculosis in pleural biopsy, or Mtb culture, and it was difficult to perform. In this case pleural fluid analysis revealed that cause of recurrent right-sided hydropneumothorax was tuberculosis infection.Summary: A 60 year old woman with four times reccurent right-sided hydropneumothorax, and the pleural fluid analysis suggested it was tuberculosis infection. Providing anti-tuberculosis medication based on clinically diagnosed tuberculosis based on flowchart of tuberculosis diagnosis from national tuberculosis programmed are essential to prevent progression of the disease.